Handbook of sport neuroscience and psychophysiology - Carlstedt, Roland A.; Balconi, Michela (New York, NY : Routledge, 2019)
"Out of the broad arena of sport science and sport psychology, Roland A. Carlstedt presents a comprehensive collection on the neuroscience and associated psychophysiology that underlies and drives sport performance. Featuring sections ranging from the basics and foundations (anatomy and physiology) to the applied (assessment during competition, training, and mental training), Handbook of Sport Neuroscience and Psychophysiology is the first volume to provide students, researchers, practitioners, and coaches the latest knowledge on the brain, mind-body processes, and psychophysiological responding in the context of sport performance" --
OCLC-licensed vendor bibliographic record.
Keywords: Sports -- Psychological aspects; Sports -- Physiological aspects; Neurosciences; GAMES / Gambling / Sports; SPORTS & RECREATION / Business Aspects; SPORTS & RECREATION / Essays; SPORTS & RECREATION / History; SPORTS & RECREATION / Reference; TRAVEL / Special Interest / Sports; PSYCHOLOGY / Applied Psychology